Lio Tribe Transmigration Women's Rights and Justice: Feminism Perspectives, Patriarchy, and Gender Stereotypes - Jagad Aditya Dewantara; Maria Rasti Tani; Rustiyarso Rustiyarso; Syamsuri Syamsuri; Afandi Afandi; Warneri Warneri (Universitas of Muhammadiyah Makassar, 2022)
His article discusses the rights and justice of transmigrated women from the Lio Tribe from a feminist perspective. The multicultural ethnic community environment requires the Lio ethnic transmigration community to mingle with the local community in Bhakti Jaya Village. The transmigration community of the Lio Tribe came and settled in Bhakti Jaya Village and continued to carry out the culture that was brought from their area of origin, giving rise to different opinions from each of the figures involved. The culture brought a marriage culture called belis. This research was conducted using an ethnographic methodology to reveal facts using observations, interviews, and documentation to collect data. The participants of this study amounted to nine people as research informants, seven people, and two local people. The study results revealed that the Lio Tribe succeeded in determining the form and number of belis by prioritizing the rights and justice that both partners must obtain. This result can also lead to household harmony for both partners, and therefore, for the transmigration community of the Lio Tribe, who are directly related to this traditional tradition, they must build good relations between the two families, both the bridal family and the inter-ethnic community. And this study shows the harmony between the Belis cultural tradition and the concept of feminism. Finally, this article provides participation to propose solutions to problems in preventing conflicts that may arise in the families involved in this traditional procession.